Grindle Policy Implementation Theory in Analysis of Forestry Conflict In Pelalawan District, Riau Province - Agung Wicaksono; Agung Wicaksono (UIR Press, 2021)
This article analyzes forestry conflicts between communities and forestry companies that occurred in Pelalawan Regency, Riau Province. Grinde's (1980) policy implementation theory is a theory that we consider appropriate for analyzing conflicts. Content of Policy includes: Interest affected, type of benefits, Extend of change envisioned, Site of decision making, Program Implementor, Resources Committed, and Context of Implementation, includes: Power, Interest, and strategies of actors involves, Institution and regime characteristics, Compliance and responsiveness we think we can analyze this conflict comprehensively. This study found that the conflict initially arose because of the centralization policy in the New Order era, which caused many forestry permits to be issued by the government without any discussion with the community. Then, the conflict intensified when the community lost a lot of economic resources that they used to get from forest resources. It is hoped that this conflict can be resolved soon so that the private sector and the community can get a win-win solution.